Development of EST‐SSR markers for diversity and breeding studies in opium poppy. Issue 3 (3rd April 2013) - Şelale, Hatice; Çelik, Ibrahim; Gültekin, Visam; Allmer, Jens; Doğanlar, Sami; Frary, Anne; Debener, T.
Abstract All publicly available opium poppy expressed sequence tag (EST) sequences, totalling 20 885, were assembled into unigenes and examined for simple sequence repeats (SSRs). Nearly 19% of the 14 957 unigenes contained SSRs with 4% harbouring more than one SSR. Average density of the SSRs was 1 SSR per 3.6 kb of non‐redundant EST sequence. Trinucleotide SSRs were most frequently identified (39%), and many of the most prevalent motifs were AT‐rich. Flanking primers were designed for 86% of the SSRs and 67 primer pairs were tested on 37 opium poppy accessions and seven related species. All markers were transferable to the related species. Polymorphism information content (PIC) values for the markers were intermediate for comparisons within opium poppy (average of 0.27) and slightly higher for comparisons across species (average of 0.29). The markers were found to be useful for diversity analysis as they successfully distinguished among Turkish opium poppy accessions and land races.